THE EFFECTIVENESS OF LEXICAL COLLOCATION EXERCISE AS PRE-LISTENING ACTIVITY IN TEACHING LISTENING COMPREHENSION - Intamanjana, Prisila Duana; Wijaya, Bambang; ., Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Â Abstract: This research aims to investigate the effectiveness of Lexical Collocation Exercise as Pre-Listening activity in teaching listening comprehension to the eleventh grade students of SMA Negeri 9 Pontianak in the academic year 2014/2015. The form of this research is pre-experimental study with one group of pre-test and post-test design. The data in this research were collected using 20 cloze passage items and 20 multiple choice items. The effect size formula was used to measure the studentsâ€™ achievement in listening comprehension. The sample of the research is 32 students. The result of data analysis shows that the effect size of the research is 2.86 which is higher than 0.5. It means that the effect size is categorized highly effective. The effect size shows that Lexical Collocation Exercise as Pre-Listening Activity in teaching listening comprehension is an effective strategy for teaching listening comprehension in the classroom. Keywords: Comprehension, Exercise, Lexical Collocation, Pre-Listening Abstrak: Penelitian ini bertujuan untuk menginvestigasi efektifitas dari latihan Lexical Collocation sebagai aktifitas pra mendengarkan dalam mengajar pemahaman mendengarkan kepada siswa kelas sebelas SMA Negeri 9 Pontianak tahun pelajaran 2014/2015. Format penelitian ini adalah pre-eksperimental dengan desain one group of pre-test and post-test. Data dikumpulkan menggunakan 20 soal teks rumpang dan 20 soal pilihan ganda. Formula efect size digunakan untuk mengukur hasil pencapaian siswa dalam pemahaman mendengarkan. Sampel penelitian terdiri dari 32 siswa. Hasil dari analisis data menunjukkan bahwa effect size dari penelitian adalah 2.86 lebih besar dari 0.5. Effect size dikategorikan sangat efektif. Hasil dari effect size menunjukkan bahwa latihan Lexical Collocation sebagai aktifitas pra listening dalam pemahaman mendengarkan merupakan strategi yang efektif untuk mengajarkan pemahaman mendengarkan di kelas. Kata kunci: Latihan, Lexical Collocation, Pemahaman, Pra-Mendengarkan